The novel mitochondria‐targeted antioxidant SkQ1 modulates angiogenesis and inflammatory micromilieu in a murine orthotopic model of pancreatic cancer. Issue 1 (4th April 2016) - Bazhin, Alexandr V.; Yang, Yuhui; D'Haese, Jan G.; Werner, Jens; Philippov, Pavel P.; Karakhanova, Svetlana
Abstract : Our understanding in the last few years about reactive oxygen species (ROS) has changed from being harmful substances to crucial intra‐ and extracellular messengers as well as important regulators controlling a wide spectrum of signaling pathways, including those in cancer immunology. Therefore, these multiple essential roles of ROS and especially of mitochondria‐derived ROS in malignant transformation and cancer progression make them a promising target for anticancer therapy. Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers in the world. A link between ROS, antioxidants and the PDAC development and progression has been recently established. Therefore, usage of specific highly efficient antioxidants could bring an option for treatment and/or prevention of PDAC. 10‐(6′‐plastoquinonyl) decyltriphenylphosphonium (SkQ1) is a new antioxidant with the highest mitochondrion membrane penetrating ability and potent antioxidant capability. In this work, we investigated an impact of SkQ1 on tumor angiogenesis, immune micromilieu, and oncological parameters in the orthotopic Panc02 murine model of PDAC. We showed that in this model SkQ1 treatment leads to the elevation of pro‐angiogenic factors and to building of mainly an anti‐inflammatory cytokine milieu. On the cellular level we showed an increase in a percentage of memory T cells and a decrease in frequency on natural killer T (NKT) cells. At the same time, SkQ1 was ineffective in the improvement of oncological parameters of PDAC‐bearing mice. New studies are needed to clarify the absence of therapeutic and/or prophylactic benefits of the antioxidant. Abstract : What's new? A recently established link between reactive oxygen species (ROS) and the development and progression of pancreatic ductal adenocarcinoma (PDAC) suggests that antioxidants could have a role in PDAC therapy. This study shows that in tumor‐bearing PDAC mice, treatment with the mitochondria‐specific antioxidant SkQ1 leads to an increase in pro‐angiogenic factors and establishes an anti‐inflammatory cytokine milieu. SkQ1 treatment further modulated immune cell composition, reducing natural killer T‐cell frequency while elevating memory CD8 T‐cell frequency. The findings suggest that antioxidant ROS regulation is a potentially effective means of modulating angiogenic and immune tumor milieu in tumor‐bearing hosts.